Classification of spin and multipolar squeezing. (17th May 2016) - Yukawa, Emi; Nemoto, Kae
Abstract: We investigate various types of squeezing in a collective su( 2 J + 1 ) system consisting of spin- J particles ( J > 1 / 2 ). We show that squeezing in the collective su( 2 J + 1 ) system can be classified into unitary equivalence classes, each of which is characterized by a set of squeezed and anti-squeezed observables forming an su(2) subalgebra in the su( 2 J + 1 ) algebra. The dimensionality of the unitary equivalence class is found to be fundamentally related to its squeezing limit. We also demonstrate the classification of squeezing among the spin and multipolar observables in a collective su(4) system.